PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Periode Tahun 2017-2021) - Riski, Ina Alfira; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to determine the effect of corporate social responsibility on firm value with profitability as a moderating variable. Disclosure of corporate social responsibility is measured through three dimensions, namely environmental disclosure (Environmental disclosure score), social disclosure (social disclosure score) and governance disclosure (government disclosure score) then firm value is measured by price book value ratio (PBV). While profitability is proxied through Return on Assets (ROA). The sample used in this study is a manufacturing company listed on the Indonesia Stock Exchange in the 2017-2021 with purposive sampling nonprobability using secondary data obtained from Bloomberg. Data analysis in this study used the Partial Least Square (PLS) approach with the Structural Equation Modeling (SEM) using SMART-PLS 4 software. The results of this study indicate that the Social Disclosure (Social Disclosure Score) influences firm value positively and significantly. Meanwhile, the variables Environmental Disclosure (Environmental disclosure score) and Governance (government disclosure score) have a negative and significant effect on firm value. Profitability is not able to strengthen the influence between the variables of Environmental Disclosure (Environmental disclosure score), Social Disclosure (Social disclosure score) on firm value but is able to moderate the influence of Governance (Governance disclosure score) on firm value